Ice Coverage Induced by Depositing a Water Drop onto the Supercooled Substrate at Extreme Low Vapor Pressure - Yugang Zhao; Zichao Zuo; Haibo Tang; Xin Zhang (Crystals, 2021)
Icing/snowing/frosting is ubiquitous in nature and industrial processes, and the accretion of ice mostly leads to catastrophic consequences. The existing understanding of icing is still limited, particularly for aircraft icing, where direct observation of the freezing dynamics is inaccessible. In this work, we investigate experimentally the impact and freezing of a water drop onto the supercooled substrate at extremely low vapor pressure, to mimic an aircraft passing through clouds at a relatively high altitude, engendering icing upon collisions with pendant drops. Special attention is focused on the ice coverage induced by an impinging drop, from the perimeter pointing outward along the radial direction. We observed two freezing regimes: (I) spread-recoil-freeze at the substrate temperature of Ts = −15.4 ± 0.2 °C and (II) spread (incomplete)-freeze at the substrate temperature of Ts = −22.1 ± 0.2 °C. The ice coverage is approximately one order of magnitude larger than the frozen drop itself, and counterintuitively, larger supercooling yields smaller ice coverage in the range of interest. We attribute the variation of ice coverage to the kinetics of vapor diffusion in the two regimes. This fundamental understanding benefits the design of new anti-icing technologies for aircraft.